PENILAIAN IMPLEMENTASI SISTEM AKUNTANSI KEUANGAN DAERAH DALAM PENGELOLAAN KEUANGAN DAERAH DI PROVINSI PAPUA BARAT (Studi Kasus di Lingkungan Sekda Provinsi Papua Barat) - , Vintina Monika Hae, S.E. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this research are (1) analyze and assess determinants factors in the financial accounting system that is human resources, leadership support, assistance, means and infrastructure, regulations and readiness, (2) examine the conformity of determinants factors in the local finance accounting system. The research method that is data used are primary data gathered directly through questionnaire and interviews from 36 SKPD consisting of cash receipts and disbursement treasurer in the Local Secretary circle of Western Papua Province The analytical tool used is quantitative descriptive analysis with percentage and quantitative descriptive by sign test. The results showed that determinants factors of the local finance l accounting system of West Papua province is 1) Human resources is assessed poorly or less appropriate 2) The leaders/superiors support were assessed good or appropriate, 3) Assistance is assessed good enough or appropriate 4) Means and infrastructure is assessed poorly or less appropriate 5) Regulation is assessed good enough or appropriate and 6) The readiness is assessed good enough or appropriate in management of the local finance based on the local finance accounting system